PELAKSANAAN PELAYANAN PRIMA DALAM MENINGKATKAN KEPUASAN MASYARAKAT (Studi kasus Pelayanan Pengurusan Kartu Keluarga di Kecamatan Menganti, Gresik) - Cintyawati, Birantika; Indartuti, Endang; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2017)
IMPLEMENTATION OF PRIMA SERVICE IN IMPROVING COMMUNITY SATISFACTION (Case Study of Family Card Handling Service in Kecamatan Menganti, Gresik)This research is meant to find out the implementation of excellent service to increased people satisfaction where the focus of the proposed research is trying to understand about the public service excellence in improving people's satisfaction at maintenance services of the Kartu Keluarga (KK). This research is associative descriptive research with quantitative approach. Survey method is done by issuing interviews and distributing questionnaires. Indicators that used in the service excellence are simplicity, clarity, certainty of time, accuracy, security, responsibility, completeness of facilities and infrastructure, ease of access, discipline, courtesy and friendliness and comfort. Indicators in the people satisfaction it can be done by measuring Indeks Kepuasan Masyarakat (IKM) i.e. the procedures, conditions of service, the clarity of service personnel, disciplinary care workers, the responsibility of service personnel, the ability of service personnel, speed of service, justice to get service, courtesy and friendliness of the clerk, reasonableness of fees service, cost of service assurance, service schedule certainty, convenience and security environment ministry. The subjects were employees of the service and the people who perform the maintenance services of Kartu Keluarga 150 respondents using quota sampling method is sampling. Based on interviews and distributed questionnaires showed that the excellent service performed by employees, especially service management to increasing People Satisfaction in District Menganti, Gresik is good and the people are satisfied with the services provided by employees.Â Keywords: Excellence Service, People Satisfaction